Kontribusi ummu salamah dalam periwayatan hadis - Alwi, Zulfahmi (PSW, 2013)
Abstract: As one af ummahat al-muminin, Ummu Salamah carried out the functionas a to the Messenger of Allah in carrying-prophetic messages andÂ provide a geat sharein the transmission of hadith. The position of Ummu salamah as the wife of Muhammad saw. made heras one of the primary resources regarding the personal life of the Prophet as well as his teachings and doctrines in Islam. Ummu Salamah has narrated not less than 809 hadith that could be found in al-kutub al- sittah. Based on that contribution, some expertsin hadith put Ummu Salamah as the most women narrators after Aisyah, that narrated hadith from Rasulullah. in terms of its content, the issues that raise din more of Ummu Salamah narrations wasaround the issuesof worship and morals ns well as muamalah.